MULTIMODAL CONSTRUCTION OF LEGAL CRITICISM IN POLITICAL CARICATURES ON INSTAGRAM @HARIANKOMPAS: ANALYSIS BY KRESS AND VAN LEEUWEN - Ita Khairani; Isni Khairina (University of Kuningan, 2026)
The transformation of digital media has expanded the space for the production and distribution of social criticism, including through political caricatures on Instagram which function as a medium for articulating public opinion on law enforcement issues. In the context of increasing scrutiny of the integrity of the apparatus, inequality in legal treatment, as well as the problem of corruption and the impact of digital technology, visual representation is an important arena in building meaning and power relations. This study aims to analyze how the discourse of criticism of law enforcement is represented and how multimodal design forms power relations in caricatures published by the Instagram account @harianKompas. The research uses a qualitative approach with the analysis of the multimodal discourse of the Kress and van Leeuwen model which includes the dimensions of discourse, design, and multimodal ensemble and cohesion. The data is in the form of four caricatures by @thomdean_cartoonist that contain issues of professionalism of the apparatus, legal disparities, bribery practices in court, and the threat of digital technology. The findings show that criticism is not conveyed explicitly through text, but rather is constructed through visual configurations such as composition, character size, facial expressions, object symbolization, and positional relationships between actors that represent power inequality. Linguistic elements function as framing reinforcements, while visual structures build a social hierarchy that places the apparatus as the dominant figure and the community as the subordinate party. Intermodal cohesion results in a construction of meaning that emphasizes irony and delegitimization of legal practices that are considered deviant. Through this study , it enriches the study of multimodal discourse analysis in the context of Indonesian social media by showing how power relations are constructed through cross-modal semiotic orchestration.